Implementation Of Banana Plant and Diseases Management Technology as An Effort to Improve Banana Producing Center Businesses In Lumajang District - Tanzil, Ahmad Ilham; Purnomo, Hari; Haryadi, Nanang Tri; Muhlison, Wildan (Talenta Publisher, 2021)
Banana is one of the leading commodities in Lumajang Distric. Partners in this service are farmer groups in Burno Village, Senduro District, Lumajang. The problem faced is the attack fungal plant pathogen caused Fusarium sp. and banana leaf-rolling caterpillar Erionota thrax. Methods in community service activities are focused on initiating groups of banana farmers, as well as providing knowledge and training on basic techniques and controlling banana pests. The steps taken include initiating the introduction of banana pests, conducting socialization and training on pest management techniques. The training conducted for partners includes a number of things, namely provision of the diversity of natural enemies, training on basic techniques for controlling pests and diseases, and training on the propagation of natural enemies, especially the fungus Trichoderma sp. and the parasitoid Trichogramma sp and their release in the field. This service is expected to be able to prevent and control banana pests and increase the amount of banana production so that it can improve welfare. Furthermore, it can improve social quality and community income